Vitamin D and COVID-19 - Aggarwal, Rashmi; Aggarwal, Hemant; Aggarwal, Rhea (International Journal of Research in Medical Sciences, 2020)
The ongoing COVID -19 pandemic is caused by severe acute respiratory syndrome corona virus -2 (SARS-CoV-2). Since its emergence in Wuhan in Hubei province of China in December 2019, the virus has spread to every continent except Antartica. Currently, there is no registered treatment or vaccine for the disease. In the current scenario of the deadly virus spreading across continents and the absence of a specific treatment of novel corona virus, there is an urgent need to search for alternative strategies to prevent and control the rapid replication of virus. Vitamin D supplementation may reduce the incidence, severity and risk of death from pneumonia (consequent to the cytokine storm) in the current COVID pandemic. Through its effect on innate and adaptive immunity, vitamin D can reduce the risk of viral respiratory tract infections. 1, 25(OH) vitamin D directly stimulates the production of anti-microbial peptides like defensin and Cathelicidin that can reduce the rate of viral replication. In addition, it can also reduce the concentration of pro-inflammatory cytokines that are responsible for causing cytokine storm and resultant fatal pneumonia. In order to reduce the risk of infection especially in developing country like India, it is recommended that people at risk of COVDI19 may be considered for vitamin D supplementation.